Kepuasan Pelanggan di Social Commerce: Tinjauan atas Ulasan Konsumen, Kemudahan Transaksi, dan Varian Produk - Didit Darmawan; Eliza Anggie (Pelantar Press, 2026)
This literature study aims to analyze the role of consumer reviews as electronic word of mouth, transaction convenience in platform architecture, and product variety as a differentiation strategy in shaping customer satisfaction in social commerce. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that consumer reviews function as an information source that reduces uncertainty and builds trust through the collective experiences of other users. Authentic, informative reviews that are responsive to potential buyers' questions reinforce positive perceptions and influence purchasing decisions. Transaction convenience encompasses all aspects of user interaction with the platform, from navigation, access speed, data security, to the availability of payment methods. Well-designed platforms create smooth and enjoyable shopping experiences. Product variety allows consumers to find products that match their specific preferences, creating a sense of personalization that increases satisfaction. These three factors reinforce each other in the unique social commerce ecosystem, where social and commercial aspects combine to create a shopping experience distinct from conventional e-commerce. This study contributes theoretically to enriching consumer behavior literature in the social commerce context and practically provides reflective foundations for business actors, platform developers, and regulators